Medial unicompartmental knee arthroplasty: increasingly uniform patient demographics despite differences in surgical volume and usage—a descriptive study of 8,501 cases from the Danish Knee Arthroplasty Registry - Henkel, Cecilie; Mikkelsen, Mette; Pedersen, Alma B; Rasmussen, Lasse E; Gromov, Kirill; Price, Andrew; Troelsen, Anders (Acta Orthopaedica, 2019)
Background and purpose — Using contemporary indications, up to 50% of patients undergoing knee arthroplasty are eligible for unicompartmental knee arthroplasty (UKA), and lower UKA use likely reflects a restrictive approach to patient selection. Since broader indications have been successfully introduced, and low surgical volume and UKA percentage (usage) are associated with higher revision rates, it is of interest whether the actual use of UKA has changed accordingly. We explored this by assessing time trends in patient demographics and whether these are associated with center UKA volume and usage. Patients and methods — From the Danish Knee Arthroplasty Registry, we included 8,501 medial UKAs performed for primary osteoarthritis during 2002–2016. Using locally weighted regression, we examined changes—both overall and by center volume and usage (low vs high)—in sex distribution, age, weight, and preoperative American Knee Society Score (AKSS-O). Results — Over the last 20 years, UKA use in Denmark has been increasing steadily. Age, weight, and proportion of men all increased regardless of volume and usage. AKSS-O showed an initial increase followed by a decrease. In lowusage and low-volume centers, the proportion of women was higher, patients were younger, weighed less, and had higher AKSS-O scores; however, for age and AKSS-O, the groups were converging during the last part of the period. Interpretation — Characteristics of UKA patients have changed in the last 15 years irrespective of center volume and usage. We found between-group differences for both volume and usage, though with convergence for age and AKSS-O, which suggests an increasingly uniform approach to patient selection.